AIDS-related Cryptococcus neoformans choroiditis. (2020) - Canfield, Gregory S.; Reingold, Sarah; Ho, Andrea; Thor, Ann D.; Pecen, Paula E.; DeSanto, Kristen; Chastain, Daniel B.; Franco-Paredes, Carlos; Castillo-Mancilla, Jose R.; Henao-Martinez, Andrés F.
Abstract: We describe a case of Cryptococcal choroiditis in a person with advanced HIV/AIDS. A 29-year-old male with AIDS presented with fever, photophobia, and ataxia secondary to cryptococcal and toxoplasma meningoencephalitis. Dilated fundoscopic examination revealed bilateral and multifocal posterior infiltrates consistent with cryptococcal choroiditis. Treatment with parenteral and intravitreal liposomal amphotericin B, oral flucytosine, and oral trimethoprim-sulfamethoxazole led to resolution of his symptoms and improvement in his vision. Our case documents a rare, intraocular opportunistic infection and highlights the importance of ophthalmologic examination in immunocompromised hosts with visual symptoms and invasive fungal infection. We discuss diagnostic and treatment considerations in cryptococcal choroiditis.